In vivo three-dimensional cephalometric landmarks using CBCT for assessment of condylar volume and surface in individuals with Class I, II, and III malocclusions - Loiola, Marlos Eurípedes de Andrade [UNESP]; Fuziy, Acácio; Higa, Rodrigo Hitoshi; Fuziy, César Henrique Fukuji [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Costa, Andre Luiz Ferreira (Taylor & Francis, 2020)
Objective: To assess volume and surface of the mandibular condyle on cone beam computed tomography (CBCT) scans by comparing Class I, II, and III malocclusions. Methods: CBCT scans of 55 patients were assessed to measure ANB angle, condyle volume, and surface by using VistaDent software. The values were compared between the different skeletal malocclusions and correlated to gender and sides. Kruskal–Wallis test was used for comparison of malocclusions and Mann–Whitney test and Wilcoxon test for comparisons of genders and sides. Statistical significance was defined as p < 0.05. Results: There were no significant differences in volume (p = 0.588) and surface (p = 0.830) between the malocclusion classes. The comparison between sides showed a statistically significant difference for surface (p = 0.038). Conclusion: Condylar volume and surface evaluated on CBCT scans showed no statistically different values for Class I, II, and III malocclusions.
Keywords: 3D imaging; Cone beam computed tomography; morphometric analysis; segmentation; temporomandibular joint